Assessment of Bifidobacterium Pseudocatenulatum G4 as A Probiotic - Mohammed Kabeir, Barka (2009)
This study has demonstrated the probiotic criteria of Bifidobacterium pseudocatenulatum G4 related to safety profile; effects on intestinal microbiota; interactions with prebiotics; and the growth in peanut milk (PM) and survivability during the storage. The safety profile of the strain G4 was evaluated in groups of BALB/c mice, fed different concentrations of Bifidobacterium strains for a period of 28 days. At the end of the experimental period, the highest dose of 11 log CFU B. pseudocatenulatum G4 /day did not affect the general health of mice nor cause any toxicity to blood based on biochemistry and haematology measurements. Pathogenicity symptoms were not detected in the internal organs; serum enzymes of liver and kidney; and histology of ceacum, ileum and colon of the treated mice; thus, the strain G4 could be a safe probiotic for food application. The effects of feeding strain G4 on selected microbiota community and metabolic activity in ceacum and colon of rats were also examined in 30 days feeding trail. The rat groups received skim milk contained either viable or metabolic product of B. pseudocatenulatum G4. The viable supplement of strain G4 increased profile of bifidobacteria, Lactobacillus and total anaerobes in ceacum and colon of the fed rats; while it decreased total aerobes and potential pathogens (staphylococcus, enterococcus and enterobacteriacea) of the same intestinal regions. However, salmonella and coliform were maintained mostly unchanged. In addition, the viable supplement of strain G4 has significantly (p< 0.05) increased short chain fatty acids (acetic, propionic, and butyric) of ceacum and colon. Commercial prebiotics [inulin and fructo-oligosaccharide (FOS)], together with sorbitol, arabinan and inoculum concentration, were tested by fractional factorial design (FFD) to determine their impact on growth of B. pseudocatenulatum G4 in skim milk (SM) medium. At 48h incubation, bacterial growth was mainly influenced by FOS and inoculum concentration. Central composite design (CCD) was adopted using FOS and inoculum concentration at 48h incubation to develop the statistical model for optimization. The model predicted that 2.46 log CFU/ml produced the optimum growth increase of B. pseudocatenulatum G4. The combination that produced the optimum point was 2.86% FOS (g/v) and 0.67% inoculum concentration (v/v). At this point of optimum combination, validation experiment recorded 2.40 ± l0.02 log CFU/ml. Further application in 1-L bioreactor for 24h showed higher growth of 2.95 log CFU/ml as compared to 2.46 CFU/ml of the optimum model prediction. The growth of strain G4 was evaluated in peanut milk (PM), and growth amounting 7.12 log CFU/ml was attained at 24h incubation. Supplementation with FOS produced growth of 8.35 log CFU/ml, which comparable to the 8.25 log CFU/ml of Trypticase phytone yeast extract (TPY) obtained at 21h incubation. During the storage of fermented PM at 25 ºC for a period of two weeks, the viable cells of strain G4 decreased to a level < 7 log CFU/ml, which did not fulfill the requirement of probiotics food. However, at two weeks refrigeration (4 ºC) storage, the viability of strain G4 was maintained high at acceptable level of > 7 log CFU CFU/ml fermented PM products. Therefore, B. pseudocatenulatum G4 assessed to be a safe probiotic microorganism for synbiotics formulation with FOS and incorporation into peanut milk (PM) for delivery purposes.